Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw dan Konvesional terhadap Hasil Belajar Fisika - Ahmad Amin; Leo Charli; Wenda Nov Fita (SPEJ (Science and Physic Education Journal), 2018)
The research aims at finding out the correlation between Jigsaw method and conventional on students learning achievement at SMP Negeri 12 Lubuklinggau. It was a quantitative research with experiment method. The population was all of the eighth grade students of SMP Negeri 12 Lubuklinggau with 156 students. The samples were the two classes which were collected by simple random sampling technique. The data collection technique was conducted through tests in the form of essay with six items and the questionnaires of learning independence. The data analysis was conducted through t test. Based on the result of posttest. Both in experiment and control class with significance level 0,05, it was found out that t obtained = 1,93 and ttable = 1,658 because t obtained > t table. It can be concluded that physic learning achievement with Jigsaw method was higher than conventional method. Keywords: Jigsaw, Learning Independence, Learning Outcomes